ANALYSIS OF BLUE ECONOMY STRATEGY IN MAINTAINING CORAL REEF BALANCE: A CASE STUDY IN AMED WATERS, BALI - Matondang, Ridwan Rafsyanjani; Efriyeldi, Efriyeldi; Thamrin, Thamrin (Lembaga Penelitian dan Pengabdian Kepada Masyarakat Universitas Riau, 2025)
Amed Waters, Bali, is one area that utilizes coral reefs in economic development. However, climate change, human activities and other factors have threatened the condition of coral reefs in Amed Waters. This study aims to determine the condition and social and economic potential of coral reefs and examine the appropriate blue economy strategy in maintaining the balance of coral reefs in Amed Waters, Bali. This research was conducted in September-November 2024. This research used direct field data collection methods such as Underwater Photo Transect (UPT), interviews and the Analytical Hierarchy Process (AHP). Based on the percentage of coral cover and the interviews' results, the results showed that coral reefs in Amed Waters can be classified as poorly damaged, so conservation efforts and sustainable management are needed to maintain the balance of coral reefs. Coral reefs have social and economic potential in the fisheries sector, with a fishing group of 19 people and marine tourism in the form of diving and snorkelling. The main focus of community economic development is the tourism sector. The blue economy strategy that can be applied in the conservation of coral reefs in Amed Waters, Bali, focuses on environmental aspects of coral reef health, economic aspects of increasing community income, and social aspects of community participation